EFEK SUKU BUNGA, NILAI TUKAR DAN EKSPOR TERHADAP CADANGAN DEVISA INDONESIA PADA MASA PANDEMI COVID-19 - Indri Rahmawati; Etty Soesilowati (STKIP Persada Khatulistiwa Sintang, 2022)
During the COVID-19 pandemic, the number of foreign exchange reserves fluctuated due to restrictions on various economic activities and macro policy adjustments by the Government. The purpose of the study was to examine how the influence of interest rate variables, the Rupiah exchange rate against the US Dollar, and exports on Indonesia's foreign exchange reserves during the covid-19 pandemic. The method applied is the Ordinary Least Square (OLS) method using the EViews 10 assistance application. The data used is monthly secondary data in the form of time series obtained from publications from Bank Indonesia and the Central Statistics Agency. The results of the study can be seen that the interest rate, exchange rate, and export variables simultaneously show a significant influence on Indonesia's foreign exchange reserves during the covid-19 pandemic. Partially, the interest rate and exchange rate variables have a significant negative effect on Indonesia's foreign exchange reserves during the COVID-19 pandemic and the export variable does not have a significant effect on Indonesia's foreign exchange reserves during the COVID-19 pandemic